A comparative cross-sectional evaluation of the Field Epidemiology Training Program-Frontline in Ethiopia - Tolcha Kebebew; Tariku Takele; Neima Zeynu; Abraham Muluneh; Medhanye Habtetsion; Jafer Kezali; Sileshi Demelash; Zewdu Assefa; Audrey E. Hu; Mahlet A. Woldetsadik; Reina M. Turcios-Ruiz; Cynthia H. Cassell; et al. (BMC, 2022)
Abstract Background The Field Epidemiology Training Program (FETP)-Frontline is a three-month in-service training aimed at improving surveillance officers' capacity to collect, analyze, and interpret surveillance data, and respond to health emergencies. We evaluated the effectiveness of the FETP-Frontline which was introduced in Ethiopia in 2016. Methods We conducted a comparative, randomized cross-sectional study to assess surveillance-related knowledge, skills, and performance among trained and untrained officers using a structured questionnaire and observation checklist. We compared the knowledge, skills, and performance scores of trained and untrained officers using the Fisher's Exact test, chi-square test, and t-test at p-value < 0.05 for statistical significance. Results We conducted the study among 74 trained and 76 untrained surveillance officers. About three-quarters of all participants were male, and the average age was 34 (± 8.6) years. Completeness and timeliness of surveillance reports were significantly higher among trained than untrained surveillance officers. The trained officers were more likely to have produced epidemiologic bulletins (55% vs 33%), conducted active surveillance six months before the survey (88% vs 72%), provided surveillance training (88% vs 65%), conducted strengths, weakness, opportunities, and threats (SWOT) analysis (55% vs 17%), and utilized Microsoft Excel to manage surveillance data (87% vs 47%). We also observed improved surveillance officers' perceived skills and knowledge, and the availability and quality of surveillance formats and reports among the trained group. Conclusions FETP-Frontline trained surveillance officers demonstrated better knowledge, skills, and performance in most surveillance activities compared to the untrained officers. FETP-Frontline can address competency gaps among district surveillance officers in Ethiopia and other countries. Scaling up the program to cover unreached districts can enable achieving the human resource development core capacity requirement of the International Health Regulations 2005.